Analysis of Seasonal Variation and Measurement of Total Ozone over Birgunj - Yadav, Ranjit Prasad (Academic Voices: A Multidisciplinary Journal, 2019)
The objective of this study was to analyze the seasonal variation and measurement of total ozone concentration (TOC) over Birgunj during one year period from February 2017 to March 2018. The measurement of TOC was made on day time period only. The daily, monthly and seasonal variations of TOC were analyzed during whole study period, the highest value of TOC is found to be 305DU in June 2017 and lowest value of TOC is 215DU in January 2018. The trend of TOC shows the seasonal pattern with maximum in summer and minimum in winter season. Specifically, high value of TOC was found in June and July and low value in December and January. The result illustrates the significant diurnal variation of total ozone with maximum at noon time and minimum at morning time and evening time. The daytime value was subjected to rather larger fluctuation due to increase solar radiation and temperature, lightning during cloudy and rainy days exhaust gases from automobile and industries.